Extracting a Fractured Lumen less Lead Wire Floating Clockwise in the Right Outflow Tract: Challenges and Complications in Pediatric Age - Siboldi, Alessandra; Falchi, Nicola; Curnis, Antonio; Formigari, Roberto (Global Journal of Medical and Clinical Case Reports, 2025)
Implantation of cardiovascular implantable electronic devices (CIEDs) in pediatric patients presents unique challenges due to anatomical and growth-related factors. Lumenless leads, designed for smaller vascular calibers, are increasingly utilized; however, their extraction may be complicated by fracture and entrapment. We report a 17-year-old male with congenitally corrected transposition of the great arteries and complete atrioventricular block who underwent multiple pacemaker implantations and revisions. Following fracture of a Medtronic 3830 lumenless ventricular lead, a residual fragment remained anchored in the left ventricular outflow tract. Years later, imaging revealed the fragment oscillating freely within the ventricular cavity. Percutaneous retrieval was successfully performed using femoral venous access with a Zurpaz Medium Curl introducer and a 15-mm Lasso Snare, achieving complete extraction without complications. This case highlights the technical challenges of extracting fractured lumenless leads in pediatric patients. Procedural success requires specialized equipment, operator expertise, and careful imaging guidance. Early recognition and management of fractured or retained leads are essential to prevent potential embolic or infectious complications in the growing pediatric population.